Laddishness Online: The possible significations and significance of 'performative shamelessness' for young women in the post-feminist context - Dobson, Amy (Routledge, 2014)
In a textual analysis of public social network site (SNS) profiles owned by young women aged between 18 and 21, many of the profiles contain representations of self which would typically be considered 'unfeminine'. Photos of young women and their friends posed with wide open mouths and protruding tongues and images depicting drunkenness and raucousness are common. This kind of 'laddish' performativity by young women leaves feminists, especially those concerned with cultural representation, with a dilemma: is 'feminist representation' to be found in this aspect of SNS representation, in this kind of 'symbolically inverted' depiction of feminine bodies? Does this kind of 'laddish' performativity by young women function less as a rebellion against femininity and more as a kind of 'giving in' to a certain model of masculinity; as a 'phallic' form of girlhood now licensed by the patriarchy; or even an indication of 'feminine melancholia', predicated on the broader cultural rejection of critical feminist voices? In this article, I suggest that neither paradigms of resistance or conformity completely suffice for understanding 'laddishness' by young women in the context of a viewing premise of self-production, such as that we encounter with SNS material. I start by offering a possible feminist reading of 'laddish' body performativity by young women on SNSs, drawing from theories of the 'grotesque body' in representation as well as from Mulvey's psychological explanation of 'voyeuristic' viewing pleasure in narrative cinema. I go on to develop the concept of 'performative shamelessness' by young women and expand upon its possible significations in the post-feminist, neoliberal cultural landscape. Engaging in particular with McRobbie's ideas about the post-feminist era, I suggest that performative shamelessness may be one of the few options available to young women wishing to maintain a sense of self-definition in the face of intense social and cultural scrutinizing, and often sexually objectifying, gazes. © 2013 © 2013 Taylor & Francis.